Analysis of Charterparty Agreements from Textual Genre and Translation Points of View - Del Pozo Triviño, Maribel (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2014)
Maritime transportation in the world today accounts for huge turnover figures and it provides sizeable commercial activity of a multicultural and multilingual nature. Most of these transactions are carried out in English, and consequently, it is not surprising that such activity generates a large amount of translation work, especially from English into other languages. One of the maritime legal documents that frequently requires translation is the Charterparty, an agreement that enables a ship-owner to charter his vessel to another party for a certain consideration. This paper focuses on the analysis of the Charterparty Agreement from a translation point of view. First, we will describe the analysis method, which is based on the concept of textual genre, and then we will proceed to a detailed analysis of the Charterparty Agreement.